(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Determinate the results of ERAS applying in osophageal cancer surgery. Methodology: Case series report, on thoracic esophageal cancer surgery with ERAS from 6/2019 to 09/2023 at Thong Nhat hospital. Result: 38 cases, the average age is 67,5 years old, men / women is 17/1. Preoperative controlling smoking addiction takes 63,6%, controlling cardiovascular condittions takes 90,9%; there are not deaths in perioiperative time. Conclusion: ERAS on esophageal cancer surgery are showed similar results with studies of other in both complications, resultes.